The influence of father involvement in early childhood care: a systematic review of factors and their impact - Nursyahbani, Coryza; Munawar, Muniroh; Hariyanti, Dwi Prasetiyawati Diyah (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Father involvement in early childhood care remains low because fathers' roles are generally limited to financial aspects, resulting in suboptimal emotional, social, and cognitive stimulation for children. Objective: This study aims to identify forms of father involvement, factors that influence it, and its impact on child development through a Systematic Literature Review (SLR) method. Methods: Articles were collected from the Google Scholar database using Publish or Perish for the period 2020–2025, resulting in 52 initial articles, which were then selected based on inclusion criteria (factors and impacts of father involvement in early childhood care) and exclusion criteria (not discussing early childhood education or not involving fathers), leaving 10 relevant articles for analysis. Result: The most dominant positive impacts of father involvement were on cognitive development (41.7%), social-emotional development (33.3%), and moral and self-identity formation (25%). The uniqueness of this study lies in its comprehensive mapping of father involvement in a multidimensional manner (physical-emotional-cognitive) and its quantitative relationship with the holistic development of children in the Indonesian cultural context. Conclusion: Overall, the SLR results emphasize the need to strengthen policies and programs for collaborative father-mother parenting to improve the quality of early childhood care and development.